Characterization of the mediator in the face of socio-environmental conflicts for ecological restoration - Pérez-Ramos, Flor Guadalupe (2023)
Human activity affects ecosystems; therefore, the search for comprehensive actions such as ecological restoration to achieve the Sustainable Development Goals continues to be a necessity. However, a first unfavorable scenario for ecological restoration in various places is socio-environmental conflicts. The solution to these problems requires the guarantee of intermediate actors. The objective was to characterize the mediator of socio-environmental conflicts for ecological restoration. In the scientific literature, the description of the mediator's juridical responsibility is limited. Six characteristics, seven functions and two objectives to be fulfilled by the mediator are considered. Among the aspects pointed out about ecological restoration, it was indicated that it implies a focus on the provision of ecosystem services and restitution in the face of biodiversity loss. Likewise, the mediator's communication is an essential key to the satisfaction of social needs and economic development based on the rational use of natural resources. It is concluded that the mediator represents the third actor during a socio-environmental conflict, but with a neutral position where its characteristics, functions and the objectives to be fulfilled allow the dialogue between the parties to guarantee the continuity of ecosystem services from ecological restoration.